Bimbingan Keagamaan Untuk Mengatasi Kecanduan Tiktok Pada Siswa - Noor, Ghaliyah; Satriah, Lilis (Irsyad: Jurnal Bimbingan, Penyuluhan, Konseling, dan Psikoterapi Islam, 2024)
The aim of this research is to determine the program, process and results of religious guidance to overcome Tiktok addiction among student at SMPN 51 Bandung. This research uses a descriptive method with a qualitative approach. The final results of the implementation of relligious guidance to overcome Tiktok addiction among students at SMPN 51 Bandung have gone well. This is proven by the implementation of programs that are based on existing problems, are easy to implement, match the vision and mission, and fulfill the program elements, namelly through religoius guidance activiteis. The implementation process is carried out using various methods such as group guidance, group counseling. The results obtained were that students’ understanding of religoius guidance achieved good results.